2019
DOI: 10.4236/jtr.2019.74022
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic Characteristics and Risk Factors Contributing Pulmonary Tuberculosis Infection and Recent Transmission

Abstract: Host factors, environmental factors, genetic diversity and distinct phylogeographic distribution of Mycobacterium tuberculosis (MTB) contribute to regional differences in drug resistance. Bangladesh remains among the top 20 high Multi drug resistant tuberculosis (MDR-TB) burden countries of the world. This cross sectional study was conducted to identify the socio demographic characteristics and the risk factors contributing Pulmonary tuberculosis (PTB) infection. These characteristics and risk factors were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…We found 66.2% MTB positive cases from urban (including metropolitan) area compared to 33.8% in rural area. This population distribution pattern was also observed by 23 . We also found 38% of EPTB cases were from middle income families (2 nd quartile of wealth index) but 45% of RR-TB cases were from high income group (3 rd quartile).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…We found 66.2% MTB positive cases from urban (including metropolitan) area compared to 33.8% in rural area. This population distribution pattern was also observed by 23 . We also found 38% of EPTB cases were from middle income families (2 nd quartile of wealth index) but 45% of RR-TB cases were from high income group (3 rd quartile).…”
Section: Resultssupporting
confidence: 78%
“…This is similar to a study conducted in India 30. But previous studies of Bangladesh among the Rifampicin resistant PTB patients showed male predominance 23,29,31 . However, the very few numbers of patients with Rifampin resistance in this study may limit the comparison between males and females.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation